Answer:
The expression that could be used is (-4)(3) + (-4)(
) ⇒ B
Step-by-step explanation:
Let us revise the distributive property:
<em>The product of a number and the sum of 2 other numbers equal to the sum of the products of the number with the other 2 numbers</em>
We will use this rule to solve the question
∵ The product of -4 and 3
= -4 × 3
→ We can right 3
as (3 +
)
∵ 3
= (3 +
)
∴ -4 × 3
= -4(3 +
)
→ By using the rule above
∵ -4(3 +
) = (-4)(3) + (-4)(
)
∴ -4 × 3
= (-4)(3) + (-4)(
)
∴ The expression that could be used is (-4)(3) + (-4)(
)
Answer:
186 cm²
Step-by-step explanation:
<em>*First we can move the shape around a bit to make it simpler to solve. If we take the triangle from the left side and move it over to the right, it connects with the other piece to create a rectangle. This leave two rectangles total which is much easier to solve.</em>
<em>*To find the length of the right rectangle, you take the 22 cm at the bottom and subtract the 12 cm (which is being used as the length for the left rectangle). This will give you a length of 10 cm long.</em>
<u>Left rectangle:</u>
A = lh
A = 12 (8)
A = 96 cm²
<u>Right rectangle:</u>
A = lh
A = 10 (9)
A = 90 cm²
<u>Total:</u>
A = 90 + 96
A = 186 cm²
Okay so just do this equation below.
92,000 x 0.06
And you have your answer!
Answer is 5,520.
Leave a 5 star rating, a thanks, and a most brainy answer!
Answer:
(y - 2)²
Step-by-step explanation:
9y² - 12y + 4 ← is a perfect square of the form
(ax - b)² = a²x² - 2abx + b²
Compare like terms with 9y² - 12y + 4, thus
a² = 9 ⇒ a = 3
b² = 4 ⇒ b = 2 and
- 2ab = - 2 × 3 × 2 = - 12
Thus
9y² - 12y + 4 = (3y - 2)²